57 Drug coated balloon only angioplasty for stent thrombosis. (4th June 2021) - Merinopoulos, Ioannis; Gunawardena, Tharusha; Corballis, Natasha; Wickramarachchi, Upul; Maart, Clint; Sreekumar, Sulfi; Sawh, Chris; Wistow, Trevor; Sarev, Toomas; Gilbert, Tim; Ryding, Alisdair; Vassiliou, Vassilios; et al.
Abstract : Introduction: Stent thrombosis, with a 5-45% mortality and 15-20% recurrence rate at 5 years, represents the most severe end of the stent failure spectrum. There are no data regarding the outcomes of patients with stent thrombosis (ST) being treated with paclitaxel drug coated balloon (DCB) angioplasty. Our aim was to determine the all-cause mortality of patients treated with DCB angioplasty for ST. Methods: We identified all patients treated for ST between June 2011 and November 2019. We excluded patients who died in the cath lab, patients with uncrossable lesions and patients who were treated with a staged CABG. The primary endpoint was all-cause mortality. The secondary endpoint was target lesion revascularisation (TLR). Survival data were obtained through the UK Health and Social Care Information Service. Clinical and angiographic data were collected from our prospectively collated database supplemented with data from electronic records where required. All angiograms were reviewed by two experienced operators to confirm ST, TIMI flow pre- and post-intervention and identify bifurcation lesions. Results: A total of 178 patients were identified; 95 treated with DCB, 35 with balloon angioplasty (BA), 26 with drug eluting stent (DES), 19 with combination of DES and DCB and 3 with thromboaspiration only. The average age was 66.2 ± 10.5 years old, while male patients accounted for 76.8%. There were a few differences between DCB, BA and DES. The DES group had more patients with history of CABG, hypertension and lower average eGFR at presentation while the DCB group had more patients with history of smoking. Importantly, the great majority of patients treated with DCB had very late ST. The patients were followed-up for an average of 45.6 ± 29.8 months; 39.8±25.4, 49.8±28.1, 57.1±40.9 months for the DCB, BA and DES groups respectively. All-cause mortality at 9 months was 8.5% for whole cohort; 7.4%, 2.9%, 19.2% for the DCB, BA and DES groups respectively (DCB vs DES p=0.07; DCB vs BA p=0.34; DES vs BA p=0.03). Table 1 shows the only independent predictors of mortality up to 5 years in multivariable Cox regression analysis.When considering only the patients discharged alive, all-cause mortality at 9 months was 4.7% for whole cohort; 5.4%, 2.9%, 8.7% for DCB, BA and DES groups respectively (no statistical difference between any pairs). There was no statistical difference in all-cause mortality ( figure 1 ) or local TLR ( figure 2 ) up to 5 years of follow-up. Conclusion: DCB-only angioplasty for patients with ST is safe and may be considered as a treatment option especially in patients with very late ST. Conflict of Interest: no conflict of interest